Racial disparities in postmastectomy breast reconstruction: National trends in utilization from 2005 to 2014. Issue 13 (16th April 2018) - Epstein, Sherise; Tran, Bao N.; Cohen, Justin B.; Lin, Samuel J.; Singhal, Dhruv; Lee, Bernard T.
Abstract : BACKGROUND: Evidence of racial disparities in the receipt of postmastectomy breast reconstruction is well documented. The objective of this study was to describe trends in racial disparities overall and by reconstructive technique. METHODS: The American College of Surgeons National Surgical Quality Improvement Program database was used to identify women who underwent mastectomy and/or breast reconstruction from 2005 to 2014. Patient demographics were recorded, and cases were grouped by reconstructive status and technique. Trends were assessed with the Cochran‐Armitage test and the index of disparity. RESULTS: Over the study period, 92, 960 postmastectomy patients were identified (77, 049 white women, 10, 396 black women, 4939 Asian women, and 576 Native American women), of whom 46, 931 underwent reconstruction. Of these, 7692 women underwent autologous reconstructions (3913 free flaps and 3696 pedicled flaps). From 2005 to 2014, receipt of breast reconstruction by postmastectomy patients rose from 33.2% to 60.0%, receipt of autologous reconstruction by patients who underwent breast reconstruction fell from 30.4% to 15.9%, and receipt of free‐flap reconstruction by patients who underwent autologous reconstruction rose from 15.0% to 70.8%. These trends were significant in all racial subgroups ( P < .001), except for Native Americans ( P = .269). The index of disparity decreased from 51.4% to 22.6% for overall receipt of breast reconstruction, decreased from 10.7% to 7.0% for tissue expander and implant‐based reconstruction, increased from 18.0% to 27.3% for autologous reconstruction, and decreased from 66.7% to 4.3% for free‐flap reconstruction. CONCLUSIONS: The use of postmastectomy breast reconstruction is steadily rising in the United States. Racial disparities persist, but progress has been made. Further efforts are needed to reduce racial disparities. Cancer 2018;124:2774‐2784 . © 2018 American Cancer Society Abstract : Evidence of racial disparities in the receipt of postmastectomy breast reconstruction is well documented. Ten years of data from the American College of Surgeons National Surgery Quality Improvement Program database demonstrate that racial disparities persist, but progress has been made.